PARTIAL AND GENERAL QUANTITATIVE CHANGES OF MORPHOLOGICAL CHARACTERISTICS IN FOOTBALL PLAYERS 14 TO 16 YEARS OF AGE - Osmo Bajrić; Munir Talović; Eldin Jelešković; Željko Kovačević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The basic aim of the research was to determine the partial and general quantitative changes (differences) of morphological characteristics that developed as a result of a specifically programmed transformational procedure in the period of six months icluding 72 training units.This research work was carried out on the sample group of football players, 14 to 16 years of age (cadets) , registered members of football clubs in the area of Srednjobosanski canton. The research applies a set of 9 variables of morphological characteristics for the evaluation of longitudinal, transverse and circular skeletal dimensionality and body mass. The analysis of possible changes (differences) between the initial and final measurements of morphological characteristics has been performed using canonic discriminant analysis and T-test for dependent sample. On the basis of obtained values of the T-test it has been established that there occurred significant postitive changes (partial transformational quantitative effects) in all the variables applied in the field of morphological characteristics as a result of the applied football programme. On the basis of obtained values of canonic discriminant analysis it has been established that the transformational programmed procedure (defined football programme) didn't result in any statistically significant general quantitative changes in the field of morphological characteristics, and that there occurred no significant discriminative function.